The omnivore at home and abroad: The value to the state of food tourism discourse of diversity. (1st June 2020) - Duffy, Andrew; Pang, Annabel
While a discourse of difference has routinely been used as a marker of national identity, such an approach is premised on exclusion. By contrast, this article considers how inclusion or diversity may be employed in nation-building discourse, and its impact on the citizenry, as embodied in the omnivore ‐ one who appreciates a wide range of cultural artefacts and, in doing so, evokes a high status. Using a Verstehen approach to critical discourse analysis, we analyse one kind of state media ‐ the Singapore Tourism Board's food-related webpages ‐ to assess how they represent citizens and tourists as culinary omnivores, and how this may be interpreted to reveal mechanisms of hegemonic state control.